ANALISIS KOMPONEN UTAMA PEMBENTUK SIKAP PETANI TERHADAP PENGEMBANGAN AGROINDUSTRI SAGU RAKYAT DI PROVINSI RIAU - Vermila, Chezy WM; Syahni, Rahmat; Khairati, Rusda; Indah Mutiara, Vonny (Universitas Medan Area, 2025)
The development of agroindustry is positively impacting the income of sago farmers. Despite the significant contribution, existing sago agroindustry experiences suboptimal due to some obstacles such as farmers' attitudes. Therefore, this research aimed to determine farmers' attitudes towards the development of sago agroindustry using several indicators. The experiment was carried out in different locations with the largest sago production, namely Tebing Tinggi Timur and Tebing Tinggi Barat Districts, Kepulauan Meranti Regency, Riau Province. The sample size comprised 100 people and the quantitative using the factor analysis method, namely Principal Component Analysis (PCA). The results of the study concluded that the development of sago agroindustry was formed from the attitude of farmers consisting of family support and gender which were included in the decision-making category group with a cumulative total variance value of 36.42%. The reference group category of 52.38% consisted of motivation, trust, and raw materials. The institutional group with the largest cumulative total variance value of 65.34% consisted of market conditions, partnerships, social and technological changes.